2012
DOI: 10.1021/la301559s
|View full text |Cite
|
Sign up to set email alerts
|

On the Influence of Surfactants on the Adsorption of Polysaccharide-Based Polymers on Cotton Studied by Means of Fluorescence Spectroscopy

Abstract: In this study, we examined the influence of surfactants on the adsorption of polymers on cotton fibers. The extent of polymer adsorption on cotton was determined directly by means of fluorescence spectroscopy using fluorescently labeled polymers. The investigation of polymer adsorption in the presence of different types of surfactants and for a large range of differently structured polymers allows us to obtain a rather general picture of this important issue. Systematic relationships between the presence of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 83 publications
(105 reference statements)
0
11
0
Order By: Relevance
“…1). 5,[70][71][72][73][74] It has been found that these complexes can be dissolved in an excess of polyelectrolyte or surfactant and their net charge has been reported to change sign in the case of JR 400-SDS, JR 400-SDBS and CMC-CTAB 14,44,80 but not in the case of CMC-DTAB, 80 for which no explanation has been advanced, yet. For mixtures of other cationic surfactants of the 1-alkyl-3-methylimidazolium bromide and N-alkyl-N-methylpyrrolidinium bromide type with CMC it has been shown that the earlier the region of the phase separation is reached the longer is the alkyl chain of the surfactant.…”
Section: Phase Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…1). 5,[70][71][72][73][74] It has been found that these complexes can be dissolved in an excess of polyelectrolyte or surfactant and their net charge has been reported to change sign in the case of JR 400-SDS, JR 400-SDBS and CMC-CTAB 14,44,80 but not in the case of CMC-DTAB, 80 for which no explanation has been advanced, yet. For mixtures of other cationic surfactants of the 1-alkyl-3-methylimidazolium bromide and N-alkyl-N-methylpyrrolidinium bromide type with CMC it has been shown that the earlier the region of the phase separation is reached the longer is the alkyl chain of the surfactant.…”
Section: Phase Behaviourmentioning
confidence: 99%
“…106 Fluorescence methods can yield useful information about polymeric systems. 107 Polysaccharide based polymers are well suited for the use of uorescence methods, since they are easy to label 108,109 and a number of studies has been performed with labeled cellulose derivatives 14,61,[110][111][112] and also with non-covalently attached uorescence labels. 102,113 Most noticeably the formation of hydrophobic surfactant aggregates along the polyelectrolyte backbone and conformational changes of hydrophobically modied cationic cellulose could be shown by the change of the uorescence signal.…”
Section: Bulk Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…with 5-[(4,6-dichlorotriazin-2-yl)amino]fluorescein (DTAF, Sigma-Aldrich) according to the procedure described by de Belder and Granath 44 and applied previously to JR 400, 30,[45][46][47] while the hydrophobic dye Atto647 was used to specifically monitor the dynamics of the surfactant aggregates. As a reference, the diffusion of the surfactant aggregates was also investigated using another hydrophobic dye, nile red (Sigma-Aldrich).…”
Section: A Materialsmentioning
confidence: 99%
“…Sensitizers, mainly surfactants, play an essential role in the dispersion of materials and controlling particle morphology. It has been reported that surfactant as a sensitizer can enhance chemiluminescence [23]. The study of fluorescence found that the sensitizing system can maintain a long fluorescence lifetime and strong luminescence intensity [24].…”
Section: Introductionmentioning
confidence: 99%